2013
DOI: 10.1002/2013ja019372
|View full text |Cite
|
Sign up to set email alerts
|

STEREO and Wind observations of intense cyclotron harmonic waves at the Earth's bow shock and inside the magnetosheath

Abstract: [1] We present the first observations of electron cyclotron harmonic waves at the Earth's bow shock from STEREO and Wind burst waveform captures. These waves are observed at magnetic field gradients at a variety of shock geometries ranging from quasi-parallel to nearly perpendicular along with whistler mode waves, ion acoustic waves, and electrostatic solitary waves. Large amplitude cyclotron harmonic waveforms are also observed in the magnetosheath in association with magnetic field gradients convected past t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 36 publications
12
66
0
Order By: Relevance
“…The long duration of the THEMIS waveform captures compared to those observed by Wind and STEREO [e.g., Breneman et al, 2013] showed that these fluctuations could remain enhanced for >10 s. We also note that the observation of these high-frequency waves was not limited to quasi-perpendicular geometry (e.g., see Table I:1 in Paper I). Thus, we conclude that large-amplitude high-frequency electromagnetic fluctuations are ubiquitous in quasi-parallel and quasi-perpendicular collisionless shocks, consistent with previous results at interplanetary shocks [e.g., Wilson et al, 2007] and the bow shock [e.g., Breneman et al, 2013].…”
Section: Energy Dissipationsupporting
confidence: 91%
See 4 more Smart Citations
“…The long duration of the THEMIS waveform captures compared to those observed by Wind and STEREO [e.g., Breneman et al, 2013] showed that these fluctuations could remain enhanced for >10 s. We also note that the observation of these high-frequency waves was not limited to quasi-perpendicular geometry (e.g., see Table I:1 in Paper I). Thus, we conclude that large-amplitude high-frequency electromagnetic fluctuations are ubiquitous in quasi-parallel and quasi-perpendicular collisionless shocks, consistent with previous results at interplanetary shocks [e.g., Wilson et al, 2007] and the bow shock [e.g., Breneman et al, 2013].…”
Section: Energy Dissipationsupporting
confidence: 91%
“…ECDI, IAWs, and trains of ESWs (similar to those shown in Figures II:5-II:7) were observed in nearly every bow shock crossing we examined with not only THEMIS, but Wind [e.g., Breneman et al, 2013] and STEREO [e.g., Breneman et al, 2013]. The amplitude of these fluctuations ranged from approximately tens of mV/m to >300 mV/m.…”
Section: Wave Propertiessupporting
confidence: 60%
See 3 more Smart Citations